2020
DOI: 10.3390/toxins12040253
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Multiple Mycotoxins in Swine, Poultry and Dairy Feeds Using Ultra High Performance Liquid Chromatography-Tandem Mass Spectrometry

Abstract: A reliable, sensitive and accurate multiple mycotoxin method was developed for the simultaneous determination of 17 mycotoxins in swine, poultry and dairy feeds using stable isotope dilution (13C-ISTD) and (ultra)-high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). A simple QuEChERS-based method (quick, easy, cheap, effective, rugged and safe) was developed consisting of soaking with a solution of 1% formic acid followed by extraction with acetonitrile, clean-up with C18 sorbent and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Second, the detection methods for these mycotoxins (including the case of multiple mycotoxins coexistence with different spp. of fungi) within dietary feeds and biological fluids, such as serum, urine, and milk, from animals [2,[22][23][24]. Third, not only feed management and control strategies for fungal infection but also the degradation approaches by physical, chemical enzymatic, and biological methods to prevent the harmful effects of mycotoxins for the animals [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the detection methods for these mycotoxins (including the case of multiple mycotoxins coexistence with different spp. of fungi) within dietary feeds and biological fluids, such as serum, urine, and milk, from animals [2,[22][23][24]. Third, not only feed management and control strategies for fungal infection but also the degradation approaches by physical, chemical enzymatic, and biological methods to prevent the harmful effects of mycotoxins for the animals [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxin B1, 3+15ADON (acetyl-deoxynivalenol), deoxynivalenol-DON, diacetoxyscirpenol-DAS, FB1, FB2, HT-2, NIV, ochratoxin A, T-2 toxin, and zearalenone (ZEA) were extracted from ground samples and quantified by UHPLC-MS/MS. The research methodology, separation chromatographs and internal standards for these mycotoxins have previously been published by Nualkaw et al [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…In food samples, fungal contamination is a common phenomenon; hence, it is the prime target for most of the work. Wang et al 235 and Nualkaw et al 236 have employed UPLC−MS for the detection of mycotoxins from animal feed like dairy product, poultry, and animal feed. Lee et al 184 reported the presence of okadaic acid, dinophysistoxin-1, dinophysistoxin-2, and dinophysistoxin-3 in raw as well as cooked mussels using LC−tandem mass spectrometry.…”
Section: Low Concentrationmentioning
confidence: 99%
“…In food samples, fungal contamination is a common phenomenon; hence, it is the prime target for most of the work. Wang et al and Nualkaw et al . have employed UPLC–MS for the detection of mycotoxins from animal feed like dairy product, poultry, and animal feed.…”
Section: Current Challenges and Future Prospectsmentioning
confidence: 99%